Revitaliser les territoires par le salariat en centre de santé. Une dynamique électorale transpartisane. - Lucas Joubert (GéoProximitéS)
The medical workforce shortage has highlighted the limitations of existing territorial health policies in France, as evidenced by ongoing access-to-care disparities. This study examines how local governments are stepping in to address this issue by establishing salaried health centers, particularly in under-resourced rural areas. Focusing on the plurality of local government initiatives, the study analyzes their electoral timing and their increasing involvement in medical workforce management—a responsibility traditionally reserved for the State. Quantitative data from FINESS and media sources illustrate the cyclical nature of these health center openings, often linked to election cycles and broader socio-political pressures. The findings reveal a transpartisan drive among municipal, departmental, and regional entities to invest in salaried medical care, presenting salaried health centers as a solution to the medical desert phenomenon.